Linking between human resource practices and job satisfaction on employee’s job performance / Nur Hidayah Ridzuan and Nurul Adawiah Amran - Ridzuan, Nur Hidayah; Amran, Nurul Adawiah (Faculty of Business and Management, 2016)
Human Resource Management can be defined as the process of planning, organizing, leading and controlling an organisation’s human resource needs to ensure both organization and employee’s satisfaction thus it will help the organization to achieve its objectives and missions. Job performance can be defined as the degree to which employees execute tasks, responsibilities, and assignments. Job performance is not only defined by action, but also judgmental and evaluative process. Job satisfaction is more narrowly defined as a pleasurable or positive emotional state resulting from the appraisal of one’s job or job experiences. The purpose of the study is to investigate the relationship between HR practices and job satisfaction on employee’s job performance. The background of HR practices philosophy, theory of job satisfaction and theory of job performance serve as starting point to develop the conceptual model. From the extensive literature review, three variable of HR practices, one variable of job satisfaction and one variable of job performance were identified to construct the model. A total of 110 completed questionnaire were returned, representing a responses rate of 83 percent. Based on data collected, an integrated structural equation of HR practices, employee’s job satisfaction and employee’s job performance was developed using five Likert-scale. The results of structural equation modelling reveal the following, training and development and satisfaction are significant to employee’s job performance in regression analysis. This conceptual model provides an understanding that a few HR practices are significant to employee’s job performance. However, job satisfaction is significant to employee’s job performance. Keywords for this project paper are Human Resource Practices, Training and Development, Compensation, Performance Appraisal, Job Performance and Job Satisfaction.